Virtual and Remote Control Tower Research, Design, Development and Validation - Fürstenau, Norbert; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The interdisciplinary research and development work carried out in the last ten years which is presented in this book aimed at replacing the conventional airport control tower by a new "remote tower operation" work environment (RTO) which should enhance work efficiency and safety and reduce costs. This revolutionary human-system interface allows for remote aerodrome traffic control without a physical tower building and enables the establishment of remote airport traffic control centers (RTC) of which each may serve several airports from a central location.
Part I Fundamentals & Preconditions -- Introduction and Overview -- Visual Features Used by Airport Tower Controllers: Some Implications for the Design of Remote or Virtual Towers -- Detection and Recognition for Remote Tower Operations -- Part II Remote Tower Simulation Environment and Remote Tower Center -- Remote Tower Simulation Environment -- Assessing Operational Validity of Remote Tower Control in High Fidelity Simulation -- Video Frame‐Rate Requirements from Visual Discrimination of Deceleration During Simulated Aircraft Landing -- Planning remote multi‐airport control - controller‐friendly assistance -- Part III RTO Engineering and Field Testing -- Augmented Vision Videopanorama Experimental System with Augmented Vision Videopanorama -- Remote Tower Prototype System and Automation Perspectives -- Which metrics provide the insight needed? A selection of remote tower evaluation metrics to support a remote tower operation concept validation -- Model-based Analysis of Two‐Alternative Decision Errors in a Videopanorama‐based Remote Tower Work Position -- Part IV Alternative Approaches and Perspectives -- The Advanced Remote Tower System and its Validation -- Remote Tower Research in the United States.
Keywords: Aerospace engineering; Astronautics; Control engineering; Computer vision; Aerospace Technology and Astronautics; Control and Systems Theory; Computer Vision